VO2 at maximal and supramaximal intensities: lessons to high-intensity interval training in swimming - Sousa, A.; Vilas-Boas, J. P.; Fernandes, R. J.; Figueiredo, P. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To establish appropriate work intensity for interval training that would elicit maximal oxygen uptake (VO2max) for well-trained swimmers.